BIOCULTURAL INTERACTIONS OF THE YAGHAN PEOPLE WITH SEAWEEDS AND MOLLUSKS: FIELD ENVIRONMENTAL PHILOSOPHY APPROACH - Ojeda Villarroel, Jaime Andrés; Rozzi Marin, Ricardo Roberto; Rosenfeld Sekulovic, Sebastián Alejandro; Contador Mejias, Tamara Andrea; Massardo Vega, Cristina Elvira Francisca; Malebran, Javiera; Gonzalez-Calderon, Julia; Mansilla Muñoz, Andres Omar (My University, 2018)
The coastal areas of the Magellan ecoregion host considerable diversity of macroalgae and mollusks. Indigenous peoples, such as the Yaghan, have developed biocultural interactions with austral coastal ecosystems. This study is an interdisciplinary ecological, ethnoecological and philosophical analysis. It applies the conceptual framework of biocultural ethics to characterize the intertidal habitat within the biocultural context of the Yaghan people. This is done through the composition of inhabitants, such as macroalgae and mollusks, linked to seasonal habits of abundance. Based on this account, we suggest methods and activities of biocultural conservations. We applied the Field Environmental Philosophy approach, which was carried out in Robalo bay, Navarino island (55 degrees S). Ecological results showed that biomass and macroalgae diversity increased in summer and decreased over the winter. Mollusks Mytilus edulis chilensis and Perumytilus purpuratus showed no seasonal variability abundance. Ethnographic results based on the literature and observant participation showed that low seasonal variability in mollusk abundance has been crucial to the subsistence of the Yaghan people. From the perspective of contemporary environmental ethics, we identified several values in the Yaghan worldview. For example, there are instrumental values in mollusks: they have been a source of food, aesthetic decoration, development of tools and building huts. We found references to the intrinsic values in mollusks, particularly in narratives and other ethnographic sources. These Yaghan values are rooted in a profound sense of empathy for biodiversity. As a result of the combined ecological, ethnographic, and philosophical issues, we suggest communication through metaphor (the submerged forest of Cape Horn) and field activities (open your eyes, dive with an open mind) for biocultural conservation.
Keywords: biocultural; environmental ethics; mollusks; macroalgae; yaghan; traditional ecological knowledge